Pemenuhan Kebutuhan Pelayanan Kepada Jemaah oleh KBIHU dan Tour & Travel Haji dan Umroh - Dwi Hanadya; Nyayu Ully Auliana (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This article examines the efforts made by the Hajj and Umrah Guidance Group (KBIHU) as well as tour and travel agents in meeting the service needs of Hajj and Umrah pilgrims. This study aims to identify the type of service provided, evaluate the quality of service, and measure the level of satisfaction of pilgrims with the services received. Data was collected through survey methods and interviews with congregations, as well as direct observation of the service process. The results of the study show that there are several important aspects in the service that are very concerned by the congregation, such as worship guidance, accommodation facilities, transportation, and health support. KBIHU and high-quality tour and travel agents are generally able to meet the expectations of pilgrims by providing comprehensive and professional services. However, there are also several obstacles and challenges faced in the service process, such as limited resources and ineffective coordination. This study suggests increasing training for service staff, improving facilities, and improving the coordination system to improve the quality of service to Hajj and Umrah pilgrims.